Social insect colonies are more likely to accept unrelated queens when they come with workers. (6th July 2021) - De Gasperin, Ornela; Blacher, Pierre; Chapuisat, Michel
Abstract: Relatedness underlies the evolution of reproductive altruism, yet eusocial insect colonies occasionally accept unrelated reproductive queens. Why would workers living in colonies with related queens accept unrelated ones, when they do not gain indirect fitness through their reproduction? To understand this seemingly paradox, we investigated whether acceptance of unrelated queens by workers is an incidental phenomenon resulting from failure to recognize non-nestmate queens, or whether it is adaptively favored in contexts where cooperation is preferable to rejection. Our study system is the socially polymorphic Alpine silver ant, Formica selysi . Within populations, some colonies have a single queen, and others have multiple, sometimes unrelated, breeding queens. Social organization is determined by a supergene with two haplotypes. In a first experiment, we investigated whether the number of reproductive queens living in colonies affects the ability of workers at rejecting alien queens, as multiple matrilines within colonies could increase colony odor diversity and reduce workers' recognition abilities. As workers rejected all alien queens, independently of the number of queens heading their colony, we then investigated whether their acceptance is flexible and favored in specific conditions. We found that workers frequently accepted alien queens when these queens came with a workforce. Our results show that workers flexibly adjust their acceptance of alien queens according to the situation. We discuss how this conditional acceptance of unrelated queens may be adaptive by providing benefits through increased colony size and/or genetic diversity, and by avoiding rejection costs linked to fighting. Abstract : Despite relatedness underlying the evolution of reproductive altruism, eusocial insect colonies sometimes host unrelated queens. We investigated whether this occurs 1) because ant workers fail at recognizing non-nestmates, or 2) because accepting unrelated queens may be adaptive. We show that workers recognize alien queens but flexibly accept them only when these queens come with a workforce, so that the potential benefits outweigh the costs of rejecting them.